CULTURAL RELEVANCE AND FAMILIAR TOPICS AS CATALYSTS FOR ESL LEARNER ENGAGEMENT: AN INVESTIGATION OF RURAL STUDENTS IN URBAN CLASSROOMS - Poduvath Abdulla (ZAMONAVIY TILSHUNOSLIK ISTIQBOLLARI: MUAMMOLAR VA YUTUQLAR MAVZUSIDA XALQARO ILMIY AMALIY ANJUMAN, 2025)
The teaching of foreign language or second language comprises various methods and approaches that aim to propel learners’ linguistic proficiency, communication skills, and autonomy. While previous studies mentioned various motivational strategies and the role of familiar topics in promoting learners’ engagement, this paper investigates how familiar topics and local culture motivate learners, especially those transitioning from rural to urban settings, to actively participate in ESL classroom. Specifically, the study examines how topics related to rural life, culture and customs make the learners more engaged in ESL speaking activities. A mixed methods approach has been employed, incorporating classroom observations and surveys to assess the learners’ participation and motivation level in response to familiar and abstract topics. The findings suggest that learners showed a higher level of enthusiasm and motivation engaging more actively in speaking activities based on familiar and culture-related topics. And it indicated a significant improvement in fluency and confidence level to initiate conversations. Ultimately, these results highlight the significance of integrating culturally and socially familiar topics into the ESL curriculum to reduce the inhibition, psychological discomfort or reluctance while speaking unfamiliar topics, among the ESL learners resulting in active participation and engagement.